HUMAN CAPITAL DEVELOPMENT STRATEGY IN THE COVID-19 PANDEMIC ERA OF MSMEs IN PANGKALPINANG CITY - Hamsani Hamsani; Reniati Reniati; Dian Prihardini Wibawa; Maya Yusnita (Integrated Journal of Business and Economics (IJBE), 2022)
As the backbone of the Indonesian economy, MSMEs continue to look for business models to achieve sustainable business performance. Human Capital is an essential factor in dealing with crises, where the Human Capital strategy consists of Knowledge, Competence, and Expertise. Therefore, the purpose of this study is to determine and analyze (1) the effect of Knowledge on Innovation, (2) the influence of Competencies on Innovation, (3) the influence of Innovation on Business Performance, and (4) the influence of Expertise on Business Performance (5) indirect effect from Transformational Leadership on the MSME scale up model through frugal innovation (6) the indirect effect of Knowledge on Business Performance through Innovation. The number of samples in this study was 101 SMEs in Pangkalpinang City. The data is processed using the Partial Least Squares analysis tool. The results of the analysis found that the Knowledge and Competencies variables have a significant influence on innovation. The innovation variable has no significant effect on Business Performance.Innovation has not significantly affected business performance because the innovations carried out are still partial and not digital-based because digital literacy is still low. On the other hand, expertise has a significant effect on Business Performance. Thus, it shows that there is a need to increase the knowledge and competence of MSME actors to become innovative. Metacognitive skills, learning skills, thinking skills, knowledge, and motivation.